Community Justice: An Emerging Field - Karp, David R. (Rowman & Littlefield Publishers, 1998)
Community justice is a phenomenon of growing interest among academics, policy makers, and criminal justice practitioners. The term reflects the increasing collaboration between criminal justice agencies and communities in the joint pursuit of public safety and a less tangible, but no less significant, pursuit of justice for victims, offenders, and all community members affected by crime. In this book, several leading scholars examine the central concerns of this emerging field. Subjects discussed include the role of community organizations in crime prevention; the structural and cultural issues underlying the concentration of race, poverty, and crime; community policing; and community prosecution and sanctioning.